L’architettura alla XXX Biennale d’arte, 1960. Carlo Scarpa e i 'bozzetti immaginari' di Erich Mendelsohn - Lanzarini, Orietta (Opus Incertum, 2024)
The Erich Mendelsohn exhibition, designed by Carlo Scarpa for the XXX Biennale in 1960, was the culmination of a long process. Efforts to include architecture exhibitions alongside those dedicated to the arts had begun in 1948, spearheaded by prominent figures such as Carlo Lodovico Ragghianti and Bruno Zevi. However, the contrast with the Milan Triennale hindered any possibility of showcasing architecture for nearly a decade. Finally, the persistent advocacy of both scholars with the Biennale’s Advisory Committee in 1958-1959 succeeded in securing the inclusion of Mendelsohn and Wright in the program for the XXX edition. Only the exhibition dedicated to the master of German Expressionism was realized, yet this milestone paved the way for the inclusion of architecture, as an official Biennale's disciplines in 1973. Scarpa designed a space that conveyed the dynamism inherent in Mendelshon’s one hundred Bozzetti immaginari (imaginary sketches); at the same time, the display devices conceived for the room allowed the sketches to be enhanced both as sequential narratives and as individual works, making them accessible to the public.